Trends in Rotation - Ghosh, R. C.; Singh, S. P. (Indian Forester, 1981)
Unlike other resource management Sciences, the management of forests to yield maximum benefits is complicated. It is on account of heterogenity in size class distributions age structure, size of the population and linkage of meaning of maximum harvest with management objectives. With the harvesting policy the concept and types of rotation thus came into existance. During early years when scientific manament was evolved, the removal was cautious and restricted to trees of higher dimensions. Rotation was in consequential and so was fixed high. In due course of time uniform system based on natural regeneration was adopted to convert a forest into a series of age blocks. As technique of management became more and more refined the rotation fell in many areas thus allowing harvest of larger quantity of material. This was followed by complete artificial planting in suitable area and led to simple system of forest management cutting down further life span 10 of a crop in which trees of merchantable dimension could be produced, Mean while production had to be stepped up not only to compensate for the land lost to competing Uses but also to satisfy the increasing demand of rising population, Side by side appropriate technologies developed for various use wood even of small sizes.So attention was paid to identify various uses and demands with the view to relate these to the capacity of forests to improve the present level of production. This led to the introduction of exotics and intensive management of indigenous species which furtber resulted in reduction in rotation. The paper also summarises the information about totation of some prominent species and ther present trends.